The Mutual Gain Perspective and Relationship between Employee Commitments to Company - Pandey, Amit (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2022)
The concept of employee-employer relations will be as old as industry inherent in industry will always be a plume of industrial life. According to industry relations, we speak of the relationships between employers and employees, which are governed by the working conditions of the employees in the organization. Therefore, this topic contains some perspective of the employees which in turn govern by the organization and totally in hand of the employer, and the employers is working on a personal relationship with the organizations and employee regulating these relationships. Keywords: Employer-Employee Relationship, Management, Financial services, Industrial Relations.